2002
DOI: 10.1111/j.2042-3306.2002.tb05391.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding exercised horses on high‐starch or high‐fat diets for 390 days

Abstract: Our hypothesis was that, because horses have not evolved as fat eaters, there may be negative metabolic long-term effects of feeding a high fat diet. The objective of the present study was to identify these long-term effects and compare them with the effects of isoenergetic long-term high starch feeding. This randomised block study with 20 exercised horses looked at the effect of feeding either a high starch (HS) or a high fat (HF) diet type in 3 periods during stabling (Stable 1), pasture, and stabling (Stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 18 publications
0
12
1
2
Order By: Relevance
“…Unlike that observed in the present study, Zeyner et al (2002) observed that in horses fed diet with 11.5% soybean oil included for 390 days, there was an increase in total solids and cholesterol concentration, with average values of 6.9 and 7.1 g/dL and 90.5 and 106.3 mg/dL, respectively, and a meaningful reduction in the urea nitrogen blood concentration in horses fed diet with soybean oil included, with average values of 35.8 and 32.1 mg/dL, respectively, without alteration in the triglyceride concentrations, with an average value of 24.4 mg/dL.…”
Section: Resultscontrasting
confidence: 57%
See 2 more Smart Citations
“…Unlike that observed in the present study, Zeyner et al (2002) observed that in horses fed diet with 11.5% soybean oil included for 390 days, there was an increase in total solids and cholesterol concentration, with average values of 6.9 and 7.1 g/dL and 90.5 and 106.3 mg/dL, respectively, and a meaningful reduction in the urea nitrogen blood concentration in horses fed diet with soybean oil included, with average values of 35.8 and 32.1 mg/dL, respectively, without alteration in the triglyceride concentrations, with an average value of 24.4 mg/dL.…”
Section: Resultscontrasting
confidence: 57%
“…Also Godoi et al (2009a) did not observe gastrointestinal disorders or alterations in the feces in horses fed diets with the addition of 19.5% soybean oil; and Zeyner et al (2002) did not observe any bad effects in horses fed diet with the addition of 11.5% soybean oil.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast to other studies reporting a negative digestibility, in a diet of mixed hay and concentrate, addition of fat in the form of soy oil, up to 15% of dry matter (DM), was reported by Zeyner et al [9] to increase fiber digestibility. Nevertheless, current studies have lacked a pure forage diet in research focused on fat supplementation.…”
Section: Introductionmentioning
confidence: 67%
“…As fat was added, decreasing dietary starch, blood glucose and insulin concentrations were also decreased according to Lindberg and Palmgren Karlsson (2001). On the other hand, an unexpected increase in concentrations of glucose was observed by Zeyner, Bessert, and Gropp (2002) from increased fat diets, but the increased glucose was attributed to an increase in the incidence of insulin resistance. Harris, Pagan, Crandell, and Davidson (1999) and Duren et al (1999), however, reported no insulin effect in horses fed diets with additional fat.…”
mentioning
confidence: 98%